2015
DOI: 10.1080/19443994.2015.1048741
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature on nutrient removal performance of a pilot-scale ABR/MBR combined process for raw wastewater treatment

Abstract: 2015):Effects of temperature on nutrient removal performance of a pilot-scale ABR/MBR combined process for raw wastewater treatment, Desalination and Water Treatment, A B S T R A C TFor the purpose of achieving relatively high efficiency, low energy demands, and easy maintenance for nutrient removal, the performance of a pilot-scale biological nutrient removal process consisting of anaerobic baffled reactor and membrane bioreactor has been evaluated for 301 d in treating two kinds of raw wastewaters. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 25 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…Also, the temperature has a significant effect on reactor treatment efficiency. Researchers [2426] had shown that treatment efficiencies of the ABR deteriorated significantly when the temperature dropped below 15°C. To overcome temperature effects, decreasing hydraulic retention times (HRT) or heating of wastewater could achieve higher removal efficiency [12], which also involves cost and energy.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the temperature has a significant effect on reactor treatment efficiency. Researchers [2426] had shown that treatment efficiencies of the ABR deteriorated significantly when the temperature dropped below 15°C. To overcome temperature effects, decreasing hydraulic retention times (HRT) or heating of wastewater could achieve higher removal efficiency [12], which also involves cost and energy.…”
Section: Introductionmentioning
confidence: 99%